2018
DOI: 10.3390/ijms19051483
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Membrane Heterogeneity Regulates Viral-Induced Membrane Fusion during HIV Entry

Abstract: Sphingomyelin- and cholesterol- enriched membrane domains, commonly referred to as “rafts” play a crucial role in a large number of intra- and intercellular processes. Recent experiments suggest that not only the volumetric inhomogeneity of lipid distribution in rafts, but also the arrangement of the 1D boundary between the raft and the surrounding membrane is important for the membrane-associated processes. The reason is that the boundary preferentially recruits different peptides, such as HIV (human immunode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…First, it has been shown that lipid-ordered (i.e. cholesterol-laden) and lipid-disordered membrane domains (also termed raft boundaries) can act as an attractor for HIV Env [29,72]. Both experimental and theoretical studies show that the presence of raft boundaries in the vicinity of HIV-1 entry sites reduces the energy barrier required to perform virus-cell fusion [21].…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been shown that lipid-ordered (i.e. cholesterol-laden) and lipid-disordered membrane domains (also termed raft boundaries) can act as an attractor for HIV Env [29,72]. Both experimental and theoretical studies show that the presence of raft boundaries in the vicinity of HIV-1 entry sites reduces the energy barrier required to perform virus-cell fusion [21].…”
Section: Discussionmentioning
confidence: 99%
“…Because the energy functional (Eq. 1) could be minimized for different peptide configurations (boundary conditions), the developed formalism is applicable for the description of a large variety of membrane proteins, including amphipathic peptides (37)(38)(39)(40) and channels.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the presence of Lo domains in the cell membrane increases the overall fusion kinetics ( Yang et al, 2016 , 2017 ). The raft boundary can act as an attractor for viral fusion peptides ( Molotkovsky et al, 2018 ).…”
Section: Membrane Rafts In Viral Entry By Fusionmentioning
confidence: 99%